The Sadness Will Not Last Forever - Dmitriev, Alexei (Russia The Netherlands, 2016)
The most beautiful paintings are those which you dream about when you lie in bed smoking a pipe, but which you never paint.
Verzio Film Festival Submission
Keywords: Documentary films